The Impact of Remittances on Growth Evidence from North African Countries - Adams, Richard (World Bank, Washington, DC, 2013)
Remittances constitute financial flows that affect the receiving country's economy and its development through diverse channels, including income, consumption, investment, government policies, potential parental absence, and removal of potential entrepreneurial individuals from the community. In view of the economic significance of remittance flows to North African economies, this paper utilizes an econometric model aimed at empirically evaluating the growth impact of remittances on four receiving economies during the period from 1980 to 2007. The model focuses on assessing the role of financial development in determining the growth impact of remittance flows to the region. The paper is organized in four main sections. Section two looks at the scope of migration movements in the four North African countries and the importance of remittance flows to the region. It shows the historical, current and future importance of remittance flows to North African economies. The third section elaborates upon what is known about the economic impacts of remittances at large. It details the major potential macroeconomic impacts of remittances through a literature review on growth and remittances. It also looks at the various channels through which remittances can impact growth. Section four presents an econometric model evaluating the growth impact of remittances with and without the financial sector variable and the results. The fifth section summarizes the main results and concludes.